Glasses in the SbPO4-WO3 system - Nalin, Marcelo [UNESP]; Poirier, G.; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; Cescato, L. (Elsevier B.V., 2007)
Glasses in the binary system (100 - x)SbPO4-xWO3 (20 <= x <= 60, x in mol%) have been prepared and characterized. Differential thermal analysis (DTA) shows that the glass transition temperature, T-g increases from 412 degrees C, for samples containing 20 mol% of WO3 to 481 degrees C observed for glass containing 60 mol%. Sample containing 40 mol% in WO3 were observed to be the most stable against devitrification. The structural organization of the glasses has been studied by using Fourier transform infra-red (FTIR), Raman, P-31 Magic angle spinning (MAS) and spin echo nuclear magnetic resonance (NMR) spectroscopies. Results suggest two distinct networks comprising the glass structure, one with high SbPO4 content and the other characteristic of the highest WO3 content samples. The glasses present photochromic properties. Colour changes are observed for samples after exposure to ultraviolet or visible laser light. XANES, at L-1 absorption edge of tungsten, suggests partial reduction from W6+ to W5+ species during the laser irradiation. The photochromic effects and the colour changes, promoted by laser excitation, are reversible and easily removed by heat for during 1 h at 150 degrees C. Subsequent 'write/erase' cycles can be done without degradation of the glasses. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: photochromics; heavy metal oxides; photoinduced effects; phosphates